The development of a BIM-enabled inspection management system for maintenance diagnoses of oil and gas plants - Chi, Hung-Lin; Wang, J.; Chai, J.; Wang, Xiangyu (2016)
Current inspection process has productivity issues, such as double handing information, timeconsuming data aggregation, lack of information transparency and so on. About inspections for plant maintenance, site managers encounter difficulties in getting global pictures tracing a significant amount of inspection information at management perspective. The decision-making is based on paperbased schedules and updated progress of them, which lacks information reliability and change flexibility. The purpose of the research-industry cooperation is to determine how the integration of inspection management and Building Information Modelling (BIM) influences the performance of the plant inspection and maintenance processes. The research team developed the integration among an online inspection management portal, a mobile client application and an existing BIM platform, NavisworksTM, in this study. By using the developed system, the information of inspection tasks, including daily status reports, schedules, and task assignments, can be linked with BIM for better visualization, communication and asset life cycle management. Site managers are able to view the inspection processes through 4D simulation identifying particular inspection tasks and time duration of their interests. The outcomes of a pilot study conducted through industrial partners shows positive comments, such as reducing time spent on aggregating inspection information, going paperless and increasing realtime inspection visibility for managers to make corresponding decisions.